An integrated in-silico Pharmaco-BioInformatics approaches to identify synergistic effects of COVID-19 to HIV patients. (March 2023) - Hossain, Md Arju; Rahman, Md Habibur; Sultana, Habiba; Ahsan, Asif; Rayhan, Saiful Islam; Hasan, Md Imran; Sohel, Md; Somadder, Pratul Dipta; Moni, Mohammad Ali
Abstract: Background: With high inflammatory states from both COVID-19 and HIV conditions further result in complications. The ongoing confrontation between these two viral infections can be avoided by adopting suitable management measures. Purpose: The aim of this study was to figure out the pharmacological mechanism behind apigenin's role in the synergetic effects of COVID-19 to the progression of HIV patients. Method: We employed computer-aided methods to uncover similar biological targets and signaling pathways associated with COVID-19 and HIV, along with bioinformatics and network pharmacology techniques to assess the synergetic effects of apigenin on COVID-19 to the progression of HIV, as well as pharmacokinetics analysis to examine apigenin's safety in the human body. Result: Stress-responsive, membrane receptor, and induction pathways were mostly involved in gene ontology (GO) pathways, whereas apoptosis and inflammatory pathways were significantly associated in the Kyoto encyclopedia of genes and genomes (KEGG). The top 20 hub genes were detected utilizing the shortest path ranked by degree method and protein-protein interaction (PPI), as well as molecular docking and molecular dynamics simulation were performed, revealing apigenin's strong interaction with hub proteins (MAPK3, RELA, MAPK1, EP300, and AKT1). Moreover, the pharmacokinetic features of apigenin revealed that it is an effective therapeutic agent with minimal adverse effects, for instance, hepatoxicity. Conclusion: Synergetic effects of COVID-19 on the progression of HIV may still be a danger to global public health. Consequently, advanced solutions are required to give valid information regarding apigenin as a suitable therapeutic agent for the management of COVID-19 and HIV synergetic effects. However, the findings have yet to be confirmed in patients, suggesting more in vitro and in vivo studies. Highlights: Clinical characteristics of HIV and COVID-19 patients, where predisposing genes, co-infection and prognosis were uncovered. Molecular docking and MDS analysis indicated that apigenin exerted effective binding capacity in COVID-19 and HIV. The targets, biological functions and signaling pathways of apigenin in HIV/COVID-19 were revealed. Five targets of apigenin in HIV/COVID-19, including MAPK1, MAPK3, EP300, RELA, and AKT1 were identified. Chord plot indicates the association between the most significant pathways and hub proteins.